Mentoring conversations in professional preparation - Tillema, HH; van der Westhuizen, G.J. (South African Journal of Higher Education, 2016)
This study focuses on the ways in which the quality of teacher education may be enhanced by mentoring. The specific focus is on the conversational strategies used by lecturer mentors and the expected and actual impact on student teacher’s learning. The notion of knowledge productivity in mentoring conversation is highlighted to emphasise the importance of mentoring to professional preparation of teachers. Using a case-design, 12 conversations between a student teacher and his/her mentor were video-recorded and analyzed with regard to conversational moves made by mentors to help students attain learning goals. This we compared with student teachers’ perceived knowledge productivity as measured in terms of stated intentions to change practices. An instrument was developed to code the conversational moves by the mentor. The case analysis controlled for the “closeness” in relationship between participants. The findings of this study suggest that: • The mentor’s approach taken during conversation differed, with the associated conversational moves, signifying how different strategies relate to the attainment of learning goals. • Conversational moves somehow did not significantly influence the student teacher’s perceived knowledge productivity. We noted two dominant moves: a scaffolding and prescriptive one, which we called the ‘high road’ approach, and an exploring one which we called the ‘low road’ approach. • Student teachers who have a closer relationship involving regular interaction with a mentor, benefitted in terms of higher knowledge productivity. Our findings indicate an overall positive effect of conversational moves on student teacher’s learning outcomes. However, almost 60% of the conversational talk were non-learning goals related, as opposed to relational talk. Closeness in the relationship was found to positively influence student teacher’s learning outcomes. No direct relation was found between specific mentor conversational moves and perceived knowledge productivity, although higher scores were found for the ‘low road’ approach.